2012
DOI: 10.1021/cn3000586
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Array of Noncovalent Interactions Impacts the Function of the 5-HT3A Serotonin Receptor in an Agonist-Specific Way

Abstract: The serotonin type 3A (5-HT 3 A) receptor is a Cysloop (pentameric) neurotransmitter-gated ion channel found in the central and peripheral nervous systems and implicated in numerous diseases. In previous studies with the endogenous agonist serotonin, we identified two interactions critical for receptor function: a cation−π interaction with W183 in loop B (TrpB) and a hydrogen bond to E129 in loop A. Here we employ mutant cycle analyses utilizing conventional and unnatural amino acid mutagenesis to demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…Loop A residue N101 couples to T6'S, supporting a previous proposition that this residue is involved in receptor gating (29). The mutation E102Q couples to T6'S, in line with a previouslypublished result (23). We observe that the T152K mutation affects ligand binding and also couples to the T6'S; thus we propose that this residue is involved in both binding and gating.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Loop A residue N101 couples to T6'S, supporting a previous proposition that this residue is involved in receptor gating (29). The mutation E102Q couples to T6'S, in line with a previouslypublished result (23). We observe that the T152K mutation affects ligand binding and also couples to the T6'S; thus we propose that this residue is involved in both binding and gating.…”
Section: Discussionsupporting
confidence: 90%
“…Previous work in the 5-HT 3A R on loop A residues N101 and E102 showed that mutations to these residues that introduce a net positive charge (N101K and E102Q) generate very large losses of function (23,29). This parallels our observation on the T152K mutation, which is the most disruptive of the single mutations in the triad swap.…”
Section: The 5-ht 3a R Triad Is Functionally Coupled To Nearby Residusupporting
confidence: 86%
See 2 more Smart Citations
“…In this analysis, the first perturbation is mutation of the protein (with conventional or non-canonical amino acids); and the second perturbation is not a mutation, but the addition of PNU-120596. Non-additivity of the two perturbations indicates that the protein mutation differentially impacts receptor function depending on whether PNU-120596 is or is not present, suggesting that the residue under study plays an important role in allosteric modulation (Daeffler, et al, 2012; Gleitsman, et al, 2009; Miles, et al, 2012). The analysis parallels that of the common double mutant cycle analysis, including the notion of an interaction energy, designated as ΔΔG.…”
Section: Introductionmentioning
confidence: 99%